Dental Caries and Tooth Brushing Practices among Students Elementary School - Utami, Sri Pandu; Mahata, Intan Batura Endo; Wiyanti, Resi (TALENTA, 2023)
Dental caries is a disease that often occurs in mid-childhood (10-12 years), which is a vulnerable period marked by the transition of milk teeth to the growth of permanent teeth. Rikesdas West Sumatra reported the experience of dental caries in 41.74% of children aged 10-14 years, with a prevalence rate in Padang City of 36.71% with the number of sufferers around 6,154 children. This quantitative research aims to determine the prevalence of dental caries and tooth brushing practices among students at SDN 27 Sungai Sapih Kuranji, Padang City. An analytical observational approach was applied, with a total of 100 students selected as respondents using total sampling techniques. Next, the data was collected from November 2022 to February 2023 and analyzed using the Spearman test, then processed using a computerized program. The results showed that the majority showed moderate tooth brushing behavior (82%), while the incidence of dental caries was relatively low (45%). Basically, a significant relationship was found between dental caries and tooth brushing practices among respondents (p = 0.001). Collaboration between dental health professionals and schools is recommended to educate students about the importance of dental and oral care, emphasizing correct toothbrushing techniques, to increase knowledge and practice of oral hygiene.